Human Capital and Production Structure: Evidence from Greece - Giouli, Eleni; Pisinas, Yorgos; Kanzola, Anna-Maria; Petrakis, Panagiotis E. (European Journal of Economics and Business Studies, 2021)
The present paper offers a theoretical review of the concept of human capital and its component elements, namely Knowledge, Skills, Abilities and Working Activities, and attempts to sketch the requirements of the production structure in the Greek economy. In addition, the role is stressed of the educational model in Greece in positively affecting the changes underway under the simultaneous impact of the 4th industrial revolution and COVID-19.
Keywords: Human Capital, 4th Industrial Revolution, Production Transformation, GreeceAcknowledgments The authors would like to thank A. Efstratoglou (PHD, INE/GSEE) for his contribution to the analysis of variables in the economy in the COVID-19 crisis. Also, the p